Pengaruh Lingkungan Internal Dan Eksternal Terhadap Minat Kunjungan Wisatawan Melalui Daya Tarik Wisata Taman Tirta Arta Di Kabupaten Sleman Yogyakarta - Ani Wijayanti - AKPAR BSI Yogyakarta (Universitas Bina Sarana Informatika, 2012)
The research is a kind of quantitative research which research many factor that influence rate of tourist visit, cover by internal environment, external environment and tourist attraction. The data collected through interviewing by spreading 200 questioner to respondence. and analyised by Structural Equation Model (SEM). The result of the research proved that internal environment had a direct effect on interest of tourist visit although indirect pass through tourist attraction and the tourist attraction itself influential to interest of tourist visit. Whereas, the external environment hadn’t an effect on interest of tourist visit whether direct or indirect pass through the tourist attraction. Based on the result of hyphotesis testing, inferential many effort could be done to increase the interest of tourist visit are increasing the human resources quality, offering the innovative and creative tourist product, building good relationship to other site for infrastructure developing as a tourist activities supporting. Besides, creating the relaxation situation to all visitor at Tirtha Artha Park. Keywords: internal environment, external environment, tourist attraction, interest of tourist visit and Tirta tour.